Method for preparing bulk and surface modified layered oxides by high temperature solid-liquid reaction and use thereof

CN117878275BActive Publication Date: 2026-10-16ZHENGZHOU UNIVERSITY OF LIGHT INDUSTRY
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
CN202311822236.9
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2023-12-27
Publication Date
2026-10-16
Estimated Expiration
2043-12-27

AI Technical Summary

Technical Problem

然而,材料在充放电过程中,钠离子的嵌入和脱出会引起结构相变,导致电极材料容量快速衰退

Benefits of technology

[0025] (1) This invention utilizes the unique properties of metal-organic framework glass materials, which have reversible solid-liquid transition and long-range structural isotropy; (2) molten metal-organic framework glass materials are used as the reaction medium and layered oxides are used as precursors; (3) by the metal-organic framework glass materials and layered oxides undergoing bulk and surface reactions in the liquid metal-organic framework glass materials, layered oxides with different bulk and surface modifications are obtained, which greatly increases the types of metal-organic framework glass modified layered oxides that can be prepared; (4) when the prepared metal-organic framework glass modified layered oxides are used as cathode materials for sodium-ion batteries, the specific capacity is close to the theoretical capacity of layered oxides, the rate performance is good, and the cycle stability is excellent.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN117878275B_ABST
    Figure CN117878275B_ABST
Patent Text Reader

Abstract

The application relates to a method for preparing a body phase and surface modified layered oxide through high-temperature solid-liquid reaction and application thereof, the method uses a molten liquid metal organic framework glass material as a reaction medium, uses a layered oxide as a precursor, and through body phase and surface reaction between the metal organic framework glass material and the layered oxide in the liquid metal organic framework glass material, a layered oxide with different body phases and surface modifications is obtained; the high-temperature molten reaction method has the advantages of directly generating an effective doped phase and a positive electrode-electrolyte interface in situ on the body phase and surface of the layered oxide particles, can simultaneously obtain a body phase with a stable structure and a positive electrode-electrolyte interface layer of organic and inorganic components, thereby stabilizing the layered oxide, and when the prepared metal organic framework glass material modified layered oxide is used as a sodium ion battery positive electrode material, the specific capacity is close to the theoretical capacity of the layered oxide, the rate performance is good, and the cyclic stability is excellent.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This invention belongs to the field of battery materials technology, specifically relating to a layered oxide prepared by high-temperature solid-liquid reaction and surface modification, and its application. Background Technology

[0002] Sodium-ion batteries possess advantages such as abundant raw material reserves and low cost, making them promising candidates for large-scale energy storage devices, such as static energy storage base stations and smart grids. Although the variety of cathode materials for sodium-ion batteries is increasing with in-depth research, developing cathode materials with high specific capacity, high power density, and excellent long-cycle stability remains crucial for their development. Currently, layered transition metal oxide materials are still the primary cathode materials for sodium-ion batteries, with their crystal structure consisting of an ordered stack of alkali metal layers and transition metal layers. However, during charge and discharge, the insertion and extraction of sodium ions cause structural phase transitions, leading to rapid capacity degradation of the electrode material. The main reasons for these structural phase transitions in layered oxide cathode materials include poor stability of the cathode-electrolyte interface, metal ion migration, and poor bulk crystal structure stability.

[0003] In recent years, bulk and surface modification have been among the most feasible strategies for improving existing sodium-ion battery cathode materials. Therefore, developing novel bulk and surface modification materials and methods is of great significance, especially those capable of simultaneously achieving in-situ modification of both bulk and surface, which holds broad promise. In-situ bulk and surface modification can achieve comprehensive cathode modification, thereby contributing to the overall improvement of sodium-ion battery performance. Summary of the Invention

[0004] The purpose of this invention is to provide a method for preparing bulk and surface-modified layered oxides via high-temperature solid-liquid reactions and their applications. Utilizing the unique properties of metal-organic framework (MOF) materials, such as reversible solid-liquid transitions and long-range structural isotropy, this invention uses molten MOF material as the reaction medium and layered oxides as precursors. Through bulk and surface reactions between the MOF material and layered oxides in the liquid MOF material, layered oxides with different bulk phases and surface modifications are obtained, significantly increasing the variety of MOF-modified layered oxides that can be prepared. Furthermore, the prepared MOF-modified layered oxides can be used as cathode materials for sodium-ion batteries.

[0005] To solve the above technical problems, the present invention adopts the following technical solution:

[0006] A method for preparing bulk and surface-modified layered oxides via high-temperature solid-liquid reaction is disclosed. This method uses molten metal-organic framework (MOF) glass as the reaction medium and layered oxides as precursors. Through bulk and surface reactions between the MOF glass and layered oxides in the liquid MOF glass, layered oxides with different bulk phases and surface modifications are obtained. This method leverages the unique properties of MOF glass, such as reversible solid-liquid transition and long-range structural isotropy. By using molten MOF glass as the reaction medium and layered oxides as precursors, the method significantly increases the variety of MOF-modified layered oxides that can be prepared. This high-temperature melt reaction method has the advantage of directly generating effective doped phases and cathode-electrolyte interfaces in situ on the bulk phase and surface of layered oxide particles, simultaneously obtaining a stable bulk phase and a cathode-electrolyte interface layer with organic and inorganic components, thereby stabilizing the layered oxides.

[0007] According to a specific and preferred aspect of the present invention, the preparation method comprises the following steps:

[0008] (1) The metal-organic framework glass material and the layered oxide are thoroughly ground and mixed, and then a high-temperature melting solid-liquid reaction is carried out under inert gas nitrogen or argon.

[0009] (2) Cool to room temperature, remove unreacted metal-organic framework glass material with N,N-dimethylformamide, and dry to obtain layered oxides modified with different metal-organic framework glass materials.

[0010] Further, in step (1), the metal-organic framework glass material is either zinc ZIF-62 glass or cobalt ZIF-62 glass; the layered oxide material is Na. 0.9 (Cu 0.22 Fe 0.3 Mn 0.48 O2 and Na 0.44 One of the types of MnO2.

[0011] Further, in step (1), the molar ratio of metal-organic framework glass material to layered oxide is (0.5-0.8):1.

[0012] Furthermore, the heating rate of the high-temperature reaction in step (1) is 5℃~10℃min. -1 .

[0013] Furthermore, the temperature of the high-temperature reaction in step (1) is 500℃~700℃, and the reaction time is 2~12 hours.

[0014] Furthermore, the drying conditions in step (2) are vacuum drying at 80°C for 12 hours.

[0015] This invention also provides bulk and surface-modified layered oxides prepared by the above method, specifically including zinc ZIF-62 glass@interstitial nitrogen-doped Na bulk phase. 0.9 (Cu 0.22 Fe 0.3 Mn 0.48 O2, Zinc ZIF-62 glass @ interstitial nitrogen bulk phase doped with Na 0.44 MnO2, cobalt ZIF-62 glass @ interstitial nitrogen-doped Na 0.9 (Cu 0.22 Fe 0.3 Mn 0.48 O2 and cobalt ZIF-62 glass @ interstitial nitrogen bulk phase doped Na 0.44 MnO2.

[0016] This invention also relates to a layered zinc oxide ZIF-62 glass with bulk and surface modification prepared above, with interstitial nitrogen-doped Na bulk phase. 0.9 (Cu 0.22 Fe 0.3 Mn 0.48 O2, Zinc ZIF-62 glass @ interstitial nitrogen bulk phase doped with Na 0.44 MnO2, cobalt ZIF-62 glass @ interstitial nitrogen-doped Na 0.9 (Cu 0.22 Fe 0.3 Mn 0.48 O2 and cobalt ZIF-62 glass @ interstitial nitrogen bulk phase doped Na 0.44 MnO2 is used as a cathode material in sodium-ion batteries.

[0017] According to one specific aspect, the following steps are taken to prepare the positive electrode sheet for a sodium-ion battery:

[0018] 1) Layered oxides modified with different metal-organic framework glass materials, acetylene black, and polyvinylidene fluoride are mixed evenly in a mass ratio of 7:2:1, and then prepared into a paste with N-methylpyrrolidone and evenly coated onto aluminum foil.

[0019] (2) Dry in a vacuum oven at 80°C for 12 hours.

[0020] The testing methods for the electrochemical performance of electrode materials are as follows:

[0021] (1) The simulated battery adopts the CR2032 button cell, in which the electrolyte is 1M sodium perchlorate in DMC, EC and EMC (volume ratio of 1:1:1) with 1% FEC added, and the negative electrode is a sodium metal sheet.

[0022] (2) The reversible capacity and cycle performance of the electrode material were tested and analyzed using constant current charge-discharge. The charge-discharge regime was: voltage range: 2.5~4.0V (for Na). 0.9 (Cu-Fe-Mn)O2 modification) and 2.0–4.0V (for Na) 0.44 (Modified with MnO2); the number of cycles is generally 1 to 2000.

[0023] The zinc ZIF-62 glass@interstitial nitrogen bulk phase doped with Na prepared in this invention 0.9 (Cu 0.22 Fe 0.3 Mn 0.48 O2, Zinc ZIF-62 glass @ interstitial nitrogen bulk phase doped with Na 0.44 MnO2, cobalt ZIF-62 glass @ interstitial nitrogen-doped Na 0.9 (Cu 0.22 Fe 0.3 Mn 0.48 O2 and cobalt ZIF-62 glass @ interstitial nitrogen bulk phase doped Na 0.44 When MnO2 is used as a cathode material for sodium-ion batteries, its specific capacity is close to that of layered oxides, it has good rate performance, and it also has excellent cycle stability.

[0024] Due to the implementation of the above technical solutions, the present invention has the following advantages compared with the prior art:

[0025] (1) This invention utilizes the unique properties of metal-organic framework glass materials, which have reversible solid-liquid transition and long-range structural isotropy; (2) molten metal-organic framework glass materials are used as the reaction medium and layered oxides are used as precursors; (3) by the metal-organic framework glass materials and layered oxides undergoing bulk and surface reactions in the liquid metal-organic framework glass materials, layered oxides with different bulk and surface modifications are obtained, which greatly increases the types of metal-organic framework glass modified layered oxides that can be prepared; (4) when the prepared metal-organic framework glass modified layered oxides are used as cathode materials for sodium-ion batteries, the specific capacity is close to the theoretical capacity of layered oxides, the rate performance is good, and the cycle stability is excellent.

[0026] In summary, the high-temperature solid-liquid reaction method of the present invention for preparing bulk and surface-modified layered oxides utilizes the unique properties of metal-organic framework (MOF) materials, namely reversible solid-liquid transition and long-range structural isotropy. Using molten MOF material as the reaction medium and layered oxides as precursors, the MOF material and layered oxides undergo bulk and surface reactions within the liquid MOF material to obtain layered oxides with different bulk phases and surface modifications. This significantly increases the variety of MOF-modified layered oxides that can be prepared. Furthermore, the prepared MOF-modified layered oxides can be used as cathode materials for sodium-ion batteries. In addition, this preparation method starts from readily available MOF materials and layered oxides, and is prepared through a highly reproducible, simple, and time-efficient process, making it highly suitable for industrial production. Attached Figure Description

[0027] Figure 1 This is a flowchart illustrating the preparation process of the bulk phase and surface-modified layered oxides of the present invention.

[0028] Figure 2 The XRD comparison diagrams of the zinc ZIF-62 glass and its corresponding ZIF-62 crystal used in Example 1 show that the zinc ZIF-62 glass has typical amorphous structure characteristics, indicating that it has a long-range isotropic lattice structure.

[0029] Figure 3 The surface-modified Na prepared in Example 1 0.9 (Cu 0.22 Fe 0.3 Mn 0.48 The XRD of O2 shows that the product retains the Na 0.9 (Cu 0.22 Fe 0.3 Mn 0.48 O2 possesses characteristic peaks in its crystal structure;

[0030] Figure 4 The surface-modified Na prepared in Example 1 0.9 (Cu 0.22 Fe 0.3 Mn 0.48 The overall scanning electron microscope image of O2 shows that the main morphology of the obtained product is irregular particles;

[0031] Figure 5 The surface-modified Na prepared in Example 1 0.9 (Cu 0.22 Fe 0.3 Mn 0.48 The micron-scale scanning electron microscope image of O2 shows that the overall morphology of the obtained product is irregular particles.

[0032] Figure 6 The surface-modified Na prepared in Example 1 0.9 (Cu 0.22 Fe 0.3 Mn 0.48 The nanoscale scanning electron microscope image of O2 shows that the surface of the obtained product has a modification layer with a thickness of nanometers. Detailed Implementation

[0033] To better understand the above-mentioned objectives, features, and advantages of this application, the application will be further described in detail below with reference to specific embodiments. Many specific details are set forth in the following description to provide a thorough understanding of this application; however, this application may also be implemented in other ways different from those described herein. Therefore, the scope of protection of this application is not limited to the specific embodiments disclosed below.

[0034] Example 1

[0035] The method for preparing bulk and surface-modified layered oxides by high-temperature solid-liquid reaction in this embodiment includes the following steps:

[0036] (1) The metal-organic framework glass material and the layered oxide were thoroughly ground and mixed. The metal-organic framework glass material was zinc ZIF-62 glass; the layered oxide material was Na 0.9 (Cu 0.22 Fe 0.3 Mn 0.48 O2; the molar ratio of metal-organic framework glass to layered oxide is 0.5:1; then a high-temperature melting solid-liquid reaction is carried out under inert nitrogen gas; the heating rate of the high-temperature reaction is 5℃ / min. -1 The high-temperature reaction was carried out at 500℃ for 12 hours.

[0037] (2) After cooling to room temperature, unreacted metal-organic framework glass material was removed using N,N-dimethylformamide, and the mixture was dried under vacuum at 80°C for 12 hours to obtain layered oxide Na modified with zinc metal-organic framework ZIF-62 glass material. 0.9 (Cu 0.22 Fe 0.3 Mn 0.48 )O2.

[0038] Figure 1 This is a schematic diagram of the specific preparation process. Figure 2The XRD patterns of the zinc ZIF-62 glass and its corresponding ZIF-62 crystal show that the zinc ZIF-62 glass exhibits typical amorphous structural characteristics, indicating that it possesses a long-range isotropic lattice structure. The layered oxide Na₂ modified with the obtained metal-organic framework glass material, zinc ZIF-62 glass, is also shown. 0.9 (Cu 0.22 Fe 0.3 Mn 0.48 The crystal structure of O2 Figure 3 ) and appearance ( Figure 4-6 Characterization revealed that the product retained Na 0.9 (Cu 0.22 Fe 0.3 Mn 0.48 O2 has characteristic peaks of crystal structure, and the main morphology of the product is irregular particles with a modification layer of nanometer thickness on the surface of the product.

[0039] The layered oxide modified with the obtained metal-organic framework glass material was used to fabricate a working electrode according to the method provided in this invention, and corresponding performance tests were performed. The electrode was tested at 50 mA g. -1 During charge and discharge, the specific capacity is close to the theoretical capacity of layered oxides; at 500 mA g -1 After 2000 charge-discharge cycles, the capacity retention rate is greater than 92%.

[0040] Example 2

[0041] The method for preparing bulk and surface-modified layered oxides by high-temperature solid-liquid reaction in this embodiment includes the following steps:

[0042] (1) The metal-organic framework glass material and the layered oxide were thoroughly ground and mixed. The metal-organic framework glass material was zinc ZIF-62 glass; the layered oxide material was Na 0.9 (Cu 0.22 Fe 0.3 Mn 0.48 O2; the molar ratio of metal-organic framework glass to layered oxide is 0.8:1; then a high-temperature melting solid-liquid reaction is carried out under inert argon gas; the heating rate of the high-temperature reaction is 10℃ / min. -1 The high-temperature reaction was carried out at 700℃ for 2 hours.

[0043] (2) After cooling to room temperature, unreacted metal-organic framework glass material was removed using N,N-dimethylformamide, and the mixture was dried under vacuum at 80°C for 12 hours to obtain layered oxide Na modified with zinc metal-organic framework ZIF-62 glass material. 0.9 (Cu 0.22 Fe 0.3 Mn 0.48 )O2.

[0044] The layered oxide modified with the obtained metal-organic framework glass material was used to fabricate a working electrode according to the method provided in this invention, and corresponding performance tests were performed. The electrode was tested at 50 mA g. -1 During charge and discharge, the specific capacity is close to the theoretical capacity of layered oxides; at 500 mA g -1 After 2000 charge-discharge cycles, the capacity retention rate is greater than 90%.

[0045] Example 3

[0046] The method for preparing bulk and surface-modified layered oxides by high-temperature solid-liquid reaction in this embodiment includes the following steps:

[0047] (1) The metal-organic framework glass material and the layered oxide were thoroughly ground and mixed. The metal-organic framework glass material was zinc ZIF-62 glass; the layered oxide material was Na 0.9 (Cu 0.22 Fe 0.3 Mn 0.48 O2; the molar ratio of metal-organic framework glass to layered oxide is 0.6:1; then a high-temperature melting solid-liquid reaction is carried out under inert nitrogen gas; the heating rate of the high-temperature reaction is 8℃ / min. -1 The high-temperature reaction was carried out at 600℃ for 5 hours.

[0048] (2) After cooling to room temperature, unreacted metal-organic framework glass material was removed using N,N-dimethylformamide, and the mixture was dried under vacuum at 80°C for 12 hours to obtain layered oxide Na modified with zinc metal-organic framework ZIF-62 glass material. 0.9 (Cu 0.22 Fe 0.3 Mn 0.48 )O2.

[0049] The layered oxide modified with the obtained metal-organic framework glass material was used to fabricate a working electrode according to the method provided in this invention, and corresponding performance tests were performed. The electrode was tested at 50 mA g. -1 During charge and discharge, the specific capacity is close to the theoretical capacity of layered oxides; at 500 mA g -1 After 2000 charge-discharge cycles, the capacity retention rate is greater than 91%.

[0050] Example 4

[0051] The method for preparing bulk and surface-modified layered oxides by high-temperature solid-liquid reaction in this embodiment includes the following steps:

[0052] (1) The metal-organic framework glass material and the layered oxide were thoroughly ground and mixed. The metal-organic framework glass material was cobalt ZIF-62 glass; the layered oxide material was Na0.9 (Cu 0.22 Fe 0.3 Mn 0.48 O2; the molar ratio of metal-organic framework glass to layered oxide is 0.5:1; then a high-temperature melting solid-liquid reaction is carried out under inert nitrogen gas; the heating rate of the high-temperature reaction is 5℃ / min. -1 The high-temperature reaction was carried out at 500℃ for 12 hours.

[0053] (2) After cooling to room temperature, unreacted metal-organic framework glass material was removed using N,N-dimethylformamide, and the mixture was dried under vacuum at 80°C for 12 hours to obtain layered oxide Na modified with cobalt ZIF-62 metal-organic framework glass material. 0.9 (Cu 0.22 Fe 0.3 Mn 0.48 )O2.

[0054] The layered oxide modified with the obtained metal-organic framework glass material was used to fabricate a working electrode according to the method provided in this invention, and corresponding performance tests were performed. The electrode was tested at 50 mA g. -1 During charge and discharge, the specific capacity is close to the theoretical capacity of layered oxides; at 500 mA g -1 After 2000 charge-discharge cycles, the capacity retention rate is greater than 93%.

[0055] Example 5

[0056] The method for preparing bulk and surface-modified layered oxides by high-temperature solid-liquid reaction in this embodiment includes the following steps:

[0057] (1) The metal-organic framework glass material and the layered oxide were thoroughly ground and mixed. The metal-organic framework glass material was cobalt ZIF-62 glass; the layered oxide material was Na 0.9 (Cu 0.22 Fe 0.3 Mn 0.48 O2; the molar ratio of metal-organic framework glass to layered oxide is 0.8:1; then a high-temperature melting solid-liquid reaction is carried out under inert argon gas; the heating rate of the high-temperature reaction is 10℃ / min. -1 The high-temperature reaction was carried out at 700℃ for 2 hours.

[0058] (2) After cooling to room temperature, unreacted metal-organic framework glass material was removed using N,N-dimethylformamide, and the mixture was dried under vacuum at 80°C for 12 hours to obtain layered oxide Na modified with cobalt ZIF-62 metal-organic framework glass material. 0.9 (Cu 0.22 Fe 0.3 Mn 0.48 )O2.

[0059] The layered oxide modified with the obtained metal-organic framework glass material was used to fabricate a working electrode according to the method provided in this invention, and corresponding performance tests were performed. The electrode was tested at 50 mA g. -1 During charge and discharge, the specific capacity is close to the theoretical capacity of layered oxides; at 500 mA g -1 After 2000 charge-discharge cycles, the capacity retention rate is greater than 95%.

[0060] Example 6

[0061] The method for preparing bulk and surface-modified layered oxides by high-temperature solid-liquid reaction in this embodiment includes the following steps:

[0062] (1) The metal-organic framework glass material and the layered oxide were thoroughly ground and mixed. The metal-organic framework glass material was cobalt ZIF-62 glass; the layered oxide material was Na 0.9 (Cu 0.22 Fe 0.3 Mn 0.48 O2; the molar ratio of metal-organic framework glass to layered oxide is 0.7:1; then a high-temperature melting solid-liquid reaction is carried out under inert argon gas; the heating rate of the high-temperature reaction is 8℃ / min. -1 The high-temperature reaction was carried out at 650℃ for 8 hours.

[0063] (2) After cooling to room temperature, unreacted metal-organic framework glass material was removed using N,N-dimethylformamide, and then dried under vacuum at 80°C for 12 hours to obtain layered oxide Na modified with metal-organic cobalt ZIF-62 framework glass material. 0.9 (Cu 0.22 Fe 0.3 Mn 0.48 )O2.

[0064] The layered oxide modified with the obtained metal-organic framework glass material was used to fabricate a working electrode according to the method provided in this invention, and corresponding performance tests were performed. The electrode was tested at 50 mA g. -1 During charge and discharge, the specific capacity is close to the theoretical capacity of layered oxides; at 500 mA g -1 After 2000 charge-discharge cycles, the capacity retention rate is greater than 91%.

[0065] Example 7

[0066] The method for preparing bulk and surface-modified layered oxides by high-temperature solid-liquid reaction in this embodiment includes the following steps:

[0067] (1) The metal-organic framework glass material and the layered oxide were thoroughly ground and mixed. The metal-organic framework glass material was zinc ZIF-62 glass; the layered oxide material was Na0.44 The molar ratio of MnO2, metal-organic framework glass, and layered oxide is 0.5:1; then a high-temperature melting solid-liquid reaction is carried out under inert nitrogen gas; the heating rate of the high-temperature reaction is 5℃ / min. -1 The high-temperature reaction was carried out at 500℃ for 12 hours.

[0068] (2) After cooling to room temperature, unreacted metal-organic framework glass material was removed using N,N-dimethylformamide, and the mixture was dried under vacuum at 80°C for 12 hours to obtain layered oxide Na modified with zinc metal-organic framework ZIF-62 glass material. 0.44 MnO2.

[0069] The layered oxide modified with the obtained metal-organic framework glass material was used to fabricate a working electrode according to the method provided in this invention, and corresponding performance tests were performed. The electrode was tested at 50 mA g. -1 During charge and discharge, the specific capacity is close to the theoretical capacity of layered oxides; at 500 mA g -1 After 2000 charge-discharge cycles, the capacity retention rate is greater than 90%.

[0070] Example 8

[0071] The method for preparing bulk and surface-modified layered oxides by high-temperature solid-liquid reaction in this embodiment includes the following steps:

[0072] (1) The metal-organic framework glass material and the layered oxide were thoroughly ground and mixed. The metal-organic framework glass material was zinc ZIF-62 glass; the layered oxide material was Na 0.44 The molar ratio of MnO2, metal-organic framework glass, and layered oxide is 0.8:1; then a high-temperature molten solid-liquid reaction is carried out under inert argon gas; the heating rate of the high-temperature reaction is 10℃ / min. -1 The high-temperature reaction was carried out at 700℃ for 2 hours.

[0073] (2) After cooling to room temperature, unreacted metal-organic framework glass material was removed using N,N-dimethylformamide, and the mixture was dried under vacuum at 80°C for 12 hours to obtain layered oxide Na modified with zinc metal-organic framework ZIF-62 glass material. 0.44 MnO2.

[0074] The layered oxide modified with the obtained metal-organic framework glass material was used to fabricate a working electrode according to the method provided in this invention, and corresponding performance tests were performed. The electrode was tested at 50 mA g. -1 During charge and discharge, the specific capacity is close to the theoretical capacity of layered oxides; at 500 mA g -1 After 2000 charge-discharge cycles, the capacity retention rate is greater than 88%.

[0075] Example 9

[0076] The method for preparing bulk and surface-modified layered oxides by high-temperature solid-liquid reaction in this embodiment includes the following steps:

[0077] (1) The metal-organic framework glass material and the layered oxide were thoroughly ground and mixed. The metal-organic framework glass material was cobalt ZIF-62 glass; the layered oxide material was Na 0.44 The molar ratio of MnO2, metal-organic framework glass, and layered oxide is 0.5:1; then a high-temperature melting solid-liquid reaction is carried out under inert nitrogen gas; the heating rate of the high-temperature reaction is 5℃ / min. -1 The high-temperature reaction was carried out at 500℃ for 12 hours.

[0078] (2) After cooling to room temperature, unreacted metal-organic framework glass material was removed using N,N-dimethylformamide, and the mixture was dried under vacuum at 80°C for 12 hours to obtain layered oxide Na modified with cobalt ZIF-62 metal-organic framework glass material. 0.44 MnO2.

[0079] The layered oxide modified with the obtained metal-organic framework glass material was used to fabricate a working electrode according to the method provided in this invention, and corresponding performance tests were performed. The electrode was tested at 50 mA g. -1 During charge and discharge, the specific capacity is close to the theoretical capacity of layered oxides; at 500 mA g -1 After 2000 charge-discharge cycles, the capacity retention rate is greater than 90%.

[0080] Example 10

[0081] The method for preparing bulk and surface-modified layered oxides by high-temperature solid-liquid reaction in this embodiment includes the following steps:

[0082] (1) The metal-organic framework glass material and the layered oxide were thoroughly ground and mixed. The metal-organic framework glass material was cobalt ZIF-62 glass; the layered oxide material was Na 0.44 The molar ratio of MnO2, metal-organic framework glass, and layered oxide is 0.8:1; then a high-temperature molten solid-liquid reaction is carried out under inert argon gas; the heating rate of the high-temperature reaction is 10℃ / min. -1 The high-temperature reaction was carried out at 700℃ for 2 hours.

[0083] (2) After cooling to room temperature, unreacted metal-organic framework glass material was removed using N,N-dimethylformamide, and the mixture was dried under vacuum at 80°C for 12 hours to obtain layered oxide Na modified with cobalt ZIF-62 metal-organic framework glass material. 0.44 MnO2.

[0084] The layered oxide modified with the obtained metal-organic framework glass material was used to fabricate a working electrode according to the method provided in this invention, and corresponding performance tests were performed. The electrode was tested at 50 mA g. -1 During charge and discharge, the specific capacity is close to the theoretical capacity of layered oxides; at 500 mA g -1 After 2000 charge-discharge cycles, the capacity retention rate is greater than 91%.

[0085] This invention leverages the unique properties of metal-organic framework (MOF) materials, including reversible solid-liquid transitions and long-range structural isotropy. Using molten MOF as the reaction medium and layered oxides as precursors, bulk and surface reactions occur between the MOF and layered oxides within the liquid MOF, yielding layered oxides with different bulk and surface modifications. This significantly increases the variety of MOF-modified layered oxides that can be prepared. Furthermore, the prepared MOF-modified layered oxides can be used as cathode materials for sodium-ion batteries. This is of great significance for promoting the synthesis of novel functional MOF-modified layered oxides and the development of high-performance sodium-ion batteries.

[0086] The above are merely preferred embodiments of this application and are not intended to limit this application. Various modifications and variations can be made to this application by those skilled in the art. Any modifications, equivalent substitutions, improvements, etc., made within the spirit and principles of this application should be included within the protection scope of this application.

Claims

1. A method for preparing bulk and surface-modified layered oxides by high-temperature solid-liquid reaction, characterized in that: This method uses molten metal-organic framework (MOF) glass as the reaction medium and layered oxides as the precursor. Through bulk and surface reactions between the MOF glass and the layered oxides in the molten MOF glass, layered oxides with different bulk phases and surface modifications are obtained. Specifically, the method includes the following steps: (1) Thoroughly grind and mix the metal-organic framework glass material and the layered oxide, and then carry out a high-temperature melting solid-liquid reaction under inert gas nitrogen or argon; (2) Cool to room temperature, remove unreacted metal-organic framework glass material with N,N-dimethylformamide, and dry to obtain layered oxides modified with different metal-organic framework glass materials.

2. The method for preparing bulk and surface-modified layered oxides by high-temperature solid-liquid reaction according to claim 1, characterized in that: In step (1), the metal-organic framework glass material is one of zinc ZIF-62 glass and cobalt ZIF-62 glass; the layered oxide material is Na. 0.9 (Cu 0.22 Fe 0.3 Mn 0.48 O2 and Na 0.44 One of the types of MnO2.

3. The method for preparing bulk and surface-modified layered oxides by high-temperature solid-liquid reaction according to claim 1, characterized in that: The molar ratio of the metal-organic framework glass material to the layered oxide in step (1) is (0.5~0.8):

1.

4. The method for preparing bulk and surface-modified layered oxides by high-temperature solid-liquid reaction according to claim 1, characterized in that: The heating rate of the high-temperature reaction in step (1) is 5 ℃~10 ℃ min. -1 .

5. The method for preparing bulk and surface-modified layered oxides by high-temperature solid-liquid reaction according to claim 1, characterized in that: The high-temperature reaction in step (1) is at a temperature of 500 ℃ to 700 ℃ and a reaction time of 2 to 12 hours.

6. The method for preparing bulk and surface-modified layered oxides by high-temperature solid-liquid reaction according to claim 1, characterized in that: The drying conditions in step (2) are vacuum drying at 80 °C for 12 hours.

7. The method for preparing bulk and surface-modified layered oxides by high-temperature solid-liquid reaction according to claim 1, characterized in that: The layered oxides with different bulk phases and surface modifications obtained in step (2) are zinc ZIF-62 glass@interstitial nitrogen bulk phase doped with Na. 0.9 (Cu 0.22 Fe 0.3 Mn 0.48 O2, Zinc ZIF-62 glass @ interstitial nitrogen bulk phase doped with Na 0.44 MnO2, cobalt ZIF-62 glass @ interstitial nitrogen-doped Na 0.9 (Cu 0.22 Fe 0.3 Mn 0.48 O2 and cobalt ZIF-62 glass @ interstitial nitrogen bulk phase doped with Na 0.44 MnO2.

8. The bulk and surface-modified layered oxides prepared by the method according to any one of claims 1 to 7.

9. The application of the bulk and surface-modified layered oxide according to claim 8 as a cathode material for sodium-ion batteries.

Citation Information

Patent Citations

  • Manganese-based metal organic framework compound-coated lithium ion battery ternary positive electrode material and preparation method thereof

    CN107910529A

  • Method for preparing boride through low-temperature melting reaction, prepared boride and application

    CN112408410A